Antitumor effects of hyaluronic acid inhibitor 4-methylumbelliferone in an orthotopic hepatocellular carcinoma model in mice - Piccioni, Flavia Valeria (2012)
Liver cirrhosis is characterized by an excessive accumulation of extracellular matrix components, including hyaluronan (HA). In addition, cirrhosis is considered a pre-neoplastic disease for hepatocellular carcinoma (HCC). Altered HA biosynthesis is associated with cancer progression but its role in HCC is unknown. 4-Methylumbelliferone (4-MU), an orally available agent, is an HA synthesis inhibitor with anticancer properties. In this work, we used an orthotopic Hepa129 HCC model established in fibrotic livers induced by thioacetamide. We evaluated 4-MU effects on HCC cells and hepatic stellate cells (HSCs) in vitro by proliferation, apoptosis and cytotoxicity assays; tumor growth and fibrogenesis were also analyzed in vivo. Our results showed that treatment of HCC cells with 4-MU significantly reduced tumor cell proliferation and induced apoptosis, while primary cultured hepatocytes remained unaffected. 4-MU therapy reduced hepatic and systemic levels of HA. Tumors systemically treated with 4-MU showed the extensive areas of necrosis, inflammatory infiltrate and 2-3-fold reduced number of tumor satellites. No signs of toxicity were observed after 4-MU therapy. Animals treated with 4-MU developed a reduced fibrosis degree compared with controls (F1-2 vs F2-3, respectively). Importantly, 4-MU induced the apoptosis of HSCs in vitro and decreased the amount of activated HSCs in vivo. In conclusion, our results suggest a role for 4-MU as an anticancer agent for HCC associated with advanced fibrosis.